FINANCIAL RATIO AND CASH FLOW VOLATILITY ANALYSIS TO DETERMINE STOCK PRICE: THE EFFECT ON BANKING STOCK RETURN IN THE PERIOD 2010 – 2019 - Chaerul Achmadi Zacky (Jurnal Ilmiah Mahasiswa FEB, 2020)
This study aims to determine the effect of financial ratios and cash flow volatility on stock returns of banking companies in 2010 - 2019. The samples were 15 banks with the largest market capitalization. The study employed quantitative approach and utilized secondary data from the sample companies’ financial statements obtained from the Indonesia Stock Exchange website. In addition, further research data were analyzed using panel regression analysis techniques with the STATA program. This study concludes that: (1) the ROA has a positive and significant effect on company stock returns; (2) LDR have a negative and significant effect on company stock returns; (3) NIM has no significant effect on company stock returns; (4) Cash Flow Volatility has a negative and significant effect on company stock returns; (5) ROA, LDR, NIM, and cash flow volatility simultaneously have a significant effect the stock returns of banking companies with a significant contribution of 22.34%.Keywords: ROA, LDR, NIM, Cash Flow Volatility, stock return, panel regression analysis.